2020
DOI: 10.1186/s43043-020-00039-y
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and the envisaged role in treating human infertility

Abstract: Background Considerable attention is being directed nowadays towards using probiotics as an alternative therapy in treating several human diseases including gastrointestinal tract diseases especially colorectal cancers, cardiovascular diseases, hyperlipidemia, and blood pressure cases. However, infertility as affected by the microbiome and the probable role of probiotics in alleviating infertility problems did not receive the deserved attention, especially in IVF patients with male or female fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Lactobacilli are the most studied probiotic bacteria, and they show several mechanisms in protecting the vaginal environment, including production of lactic acid that deters pathogens by lowering the pH and yielding an acidic environment to the cervico-vaginal mucus [ 27 ]; production of bacteriocins, which are antimicrobial peptides and proteins that protect against microbial invasion; and enhancement of immunomodulation by producing H 2 O 2 and stimulating anti-inflammatory action [ 28 ]. In a recent review article, Younis et al drew attention to the importance of further exploring in future clinical research the role of probiotics in managing infertility [ 29 ]. Bhandari et al demonstrated that Lactobacillis plantarum works to competitively exclude sperm-agglutinating Escherichia coli ( E. coli ) bacteria.…”
Section: Infertilitymentioning
confidence: 99%
“…Lactobacilli are the most studied probiotic bacteria, and they show several mechanisms in protecting the vaginal environment, including production of lactic acid that deters pathogens by lowering the pH and yielding an acidic environment to the cervico-vaginal mucus [ 27 ]; production of bacteriocins, which are antimicrobial peptides and proteins that protect against microbial invasion; and enhancement of immunomodulation by producing H 2 O 2 and stimulating anti-inflammatory action [ 28 ]. In a recent review article, Younis et al drew attention to the importance of further exploring in future clinical research the role of probiotics in managing infertility [ 29 ]. Bhandari et al demonstrated that Lactobacillis plantarum works to competitively exclude sperm-agglutinating Escherichia coli ( E. coli ) bacteria.…”
Section: Infertilitymentioning
confidence: 99%
“…The manipulation of the microbiota existing in the reproductive tract of both males and females can be an effective tool to control many reproductive diseases and associated infertility. Reproductive outcomes in both humans [39,40] and animal models [14,41] may be improved by decreasing the proportion of dysbiotic microorganisms and microbial pathogens in the reproductive tract and increasing the proportion of symbiotic microorganisms. According to this concept, the use of antibiotics and the use of probiotics are basically two approaches that may be used to manage reproductive tract microbiota.…”
Section: Manipulation Of Reproductive Tract Microbiotamentioning
confidence: 99%
“…These studies have supported the use of probiotics-based therapy as a potential tool to enhance reproductive efficiency and to tackle infertility in males. Probiotics have been demonstrated to improve spermatogenesis, epididymal sperm count, and normal sperm percentage and to reduce the percentage of sperm morphological abnormalities and DNA damage in mammalian species, including humans [39].…”
Section: Men's Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…plays a crucial role in avoiding the invasion of pathogenic bacteria and dysbiosis of native microbiota [ 6 ]. These lactic acid bacteria's influence on fertility and their role in promoting fecundity could be discussed from two main perspectives: first, male fertility and the potential antioxidant impact of lactic acid bacteria on sperm parameters, testicular histopathology, and testosterone level and second, female fertility and the effect of lactic acid bacteria on maintaining the bacterial balance in the vagina, treatment of bacterial vaginosis, and the subsequent effect on amelioration of bacterial vaginosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%